Políticas sociales y reforma institucional en la Cuba pos-COVID - Hoffmann, Bert (Verlag Barbara Budrich, 2021)
The economic crisis in the wake of the COVID pandemic is putting Cuba's socialism to a severe test. The government in Havana has put a reform of the economy, institutional structure and social policies on the agenda. This volume brings together contributions from leading international experts as well as from the island itself, analysing the economic, political and social challenges facing Cuba today.